Aging-effect in optimal doped Yba₂Cu₃O₇₋δ single crystals - Nazyrov, Z.F.; Popova, A.V.; Vovk, R.V. (Functional Materials, 2014)
We investigate the conducting properties of the optimally oxygen doped YBa₂Cu₃O₇₋δ single crystals in the basal ab-plane before and after a long time exposure (aging) at air atmosphere. Prolonged exposure leads to increase of amount of the effective scattering centers of the normal carriers. The excess conductivity in a wide temperature range has exponential temperature dependence and near the critical temperature (Tc) is well described within the Aslamazov-Larkin theoretical model. Here we show that the prolonged exposure leads to a great extention of temperature range of the pseudogap state implementation and to narrowing the linear section of the dependence ρab(T).